Paraganglioma of the left common iliac artery: case report and review of the literature - Kumari, Garima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Paraganglioma is a neoplasm derived from the neural crest of the neuroendocrine system. Head and neck account for its more frequent localizations. Parasymphatic paraganglioma have been encountered at cauda equina and iliac vessels. A 37–year old female patient with abdominal pain diagnosed as adnexal mass was surgically operated on at the SMS medical college and research group in Jaipur, Rajasthan, India. During surgery, a retroperitoneal mass was found located lateral to the common left iliac artery. It was completely resected. Microscopic study established characteristics of paraganglionoma. Patient outcome was good. Scanning for other tumour site was negative.